Long term exposure of 900-1800 MHz mobile phone radiation on mice liver - A histological study - N Mugunthan; K Shanmuga Samy; J Anbalagan; S Meenachi (Wolters Kluwer Medknow Publications, 2016)
Background and aims: Rapid developments in the telephone technology has made the communication faster and easier. The duration of the usage of mobile phones has also increased beyond the limits, which has raised the public concerns about their safety. This study was designed to investigate the long term exposure of 900 MHz to 1800 MHz mobile phone radiation induced structural changes in the mice liver at histological level. Materials & methods: After approval of institutional animal ethics committee, 36 mice were exposed to 2G (900-1800 MHz) mobile phone radiation, 48 minutes per day for a period of 30 to 180 days. The sham exposed group of 36 mice were kept under similar conditions without 2G exposure. The animals were sacrificed and the liver was removed after 1-6 months. The weight and volume of liver were recorded and the liver tissue was processed for histological study. The sections were studied under light microscope for structural changes. Two groups' data were compared and analyzed statistically. Results: Liver of 2G exposed groups showed the following findings in comparison to sham exposed group: Liver parenchyma and the periportal regions were infiltrated with lymphocytes, macrophages and neutrophil (mixed type of inflammation). Focal hemorrhages were found within the liver parenchyma. Hepatic sinusoids were congested and dilated. Many hepatocytes were swollen and showed pyknotic nuclei andvacuolations present in the cytoplasm. Conclusion: The long term exposure of ultra-high frequency radiation emitted from 2G cell phone can cause microscopic changes in the liver.